Effects of mobile learning in medical education: a counterfactual vvaluation - Briz-Ponce, L (2018)
The aim of this research is to contribute to the general system education providing new insights and resources. This study performs a quasi-experimental study at University of Salamanca with 30 students to compare results between using an anatomic app for learning and the formal traditional method conducted by a teacher. The findings of the investigation suggest that the performance of learners using mobile apps is statistical better than the students using the traditional method. However, mobile devices should be considered as an additional tool to complement the teachers’ explanation and it is necessary to overcome different barriers and challenges to adopt these pedagogical methods at University.